1998
DOI: 10.1002/(sici)1096-8652(199807)58:3<235::aid-ajh13>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Solitary extramedullary plasmacytoma in the retroperitoneum

Abstract: Solitary extramedullary plasmacytoma is an uncommon neoplasm and occurs most frequently in the upper respiratory tract. Herein, we reported a solitary extramedullary plasmacytoma in the retroperitoneum. A 28-year-old man presented with obstructive jaundice and a retroperitoneal tumor. Ultrasound-guided biopsy confirmed that the lesion was a plasma cell neoplasm. A detailed investigation showed that no other sites were involved. The tumor got a moderate reduction following local irradiation, and a complete remi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…Most human EMPs are in the upper respiratory tract, oral cavity, or gastrointestinal tract. 9,27 Human cutaneous plasmacytomas are rare and usually solitary; visceral metastases or progression to multiple myeloma is observed in one third of cases. 56,57 Immunohistochemical detection of immunoglobulin heavy and light chains has been the standard test for plasma cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most human EMPs are in the upper respiratory tract, oral cavity, or gastrointestinal tract. 9,27 Human cutaneous plasmacytomas are rare and usually solitary; visceral metastases or progression to multiple myeloma is observed in one third of cases. 56,57 Immunohistochemical detection of immunoglobulin heavy and light chains has been the standard test for plasma cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…CD20 is expressed from the pre-Bcell stage to the activated B-cell stage 23 and is not detected in human EMPs or multiple myelomas, although a few normal plasma cells can show reactivity. 9,27,28,55 Typically, human plasmacytomas have a MUM1/IRF4…”
Section: Discussionmentioning
confidence: 99%
“…Solitary EMP rarely occurs in the retroperitoneum. Cases of retroperitoneal EMP have different clinical manifestations, such as renal failure due to bilateral renal vein occlusion [6] , flank pain, hematuria due to thrombosis of the renal vein [7] , obstructive jaundice [8] , abdominal distention and pain [9,10] , and hyperamylasemia [11] . However, our patient presented with only abdominal distention and effort intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that there is no evidence that retroperitoneal EMP progresses one year after chemotherapy in combination with radiotherapy [14] . Chen et al [8] have reported a case of retroperitoneal EMP accompanying obstructive jaundice, who showed a complete response to sequential radiotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…An e-database search revealed six documented cases of retroperitoneal EMPs. They manifested as renal failure due to bilateral renal vein occlusion [3], flank pain and hematuria due to thrombosis of the renal vein [4], obstructive jaundice [5], and abdominal distention and pain [6][7][8]. The differential diagnosis of retroperitoneal EMPs include lymphoplasmacytic lymphoma and immunoblastic lymphoma [8,9].…”
Section: To the Editormentioning
confidence: 99%